Radiological risks in Nasser lake water and their health and environmental implications - Khaled Ali; Ahmed Abu-Taleb; Abd El-Baset Abbady; Shaban Harb (Scientific Reports)
Abstract This study aimed to evaluate the activity concentrations of naturally occurring radionuclides (NORs) in Nasser Lake water, assess the associated radiological risks, and investigate the potential health and environmental impacts. The presence of these NORs is attributed to both natural geological formations, such as uranium-rich granitic and metamorphic rocks, and anthropogenic activities, including agricultural runoff. Water samples were analyzed for radium-226 (Ra-226), thorium-232 (Th-232), and potassium-40 (K-40). The Ra-226 concentration ranged from 0.08 ± 0.003 to 1.28 ± 0.06 becquerel per liter (Bq/l), mostly between 0.2 and 1.0 Bq/l, reflecting geological and anthropogenic influences. The symbol (±) represents the measurement uncertainty associated with gamma spectrometric analysis. According to international radiation safety guidelines, Ra-226 levels below 1 Bq/l are considered safe for consumption. The Th-232 concentration varied from 0.04 ± 0.001 to 0.96 ± 0.06 Bq/l, showing significant spatial variation. Similarly, K-40 concentrations ranged from 1.35 ± 0.11 to 16.57 ± 1.43 Bq/l, with some notably high values. The annual effective dose (E ff ) ranged from 15.8 to 266.15 micro sievert per year (µSv/y) for adults, reaching 362.92 µSv/y for children and 221.54 µSv/y for infants. The doses for children and infants exceeded the recommended thresholds. Cancer risk (CR) assessments showed that men’s mortality risks ranged from 2.56 × 10−5 to 4.10 × 10−4, while women’s ranged from 2.68 × 10−5 to 4.29 × 10−4. Morbidity risks varied between 3.72 × 10−5 and 5.95 × 10−4 for men and 3.89 × 10−5 to 6.22 × 10−4 for women. These risks correlate with specific lake locations, highlighting hot spots with elevated radioactive content. Water acidity levels (pH) ranged from 6.23 to 7.9, indicating predominantly neutral to slightly alkaline conditions. These variations correlated with electrical conductivity (EC), reflecting complex interaction between pH, EC, and NORs. The study assesses gamma radiation hazards from external exposure and internal risks from alpha-emitting radionuclides, such as Ra-226 and Th-232, through water ingestion. While most samples comply with standard radiation limits, elevated radionuclide levels in certain areas pose potential health risks, particularly for vulnerable populations like children. Continuous monitoring of radiological parameters in Naser Lake is essential to trace long-term trends and ensure safety compliance. Additionally, advanced water treatment methods could help mitigate radionuclide concentrations in affected areas.